2022
DOI: 10.3390/microorganisms10020331
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Data on the Occurrence of Anisakis spp. in European Hake (Merluccius merluccius) Caught Off the Portuguese Coast and on Reports of Human Anisakiosis in Portugal

Abstract: Parasitic nematodes of the genus Anisakis are among the most important biological hazards associated with seafood. A survey of Anisakis spp. in European hake (Merluccius merluccius) was undertaken as this species is a staple of the Portuguese diet. Moreover, a literature review of cases of anisakiosis reported from Portugal, a country with one of the highest levels of fish consumption in the world, was also carried out. Seventy-five European hake caught in the Atlantic Ocean off the northern coast of Portugal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
8
1
Order By: Relevance
“…The analysis of the fish catching season on larvae parasitization, mainly on Anisakis larvae showed a similar pattern in the three populations of hakes, with the autumn-winter period reaching the highest parasitization parameters, prevalence and mean abundance, compared to the spring-summer period, with or without statistically significant differences. However, these results are not in accordance with those reported in previous studies in this and other fish species previously analysed, which reported mainly, the highest parasitization parameters during the spring season [12,18,22,36,44,45]. Only a few studies reported a higher parasitation in fish caught during the autumn season, such as in the silver hake [1,12].…”
Section: Influence Of the Of Fish Catching Season On Anisakis Parasit...contrasting
confidence: 96%
See 2 more Smart Citations
“…The analysis of the fish catching season on larvae parasitization, mainly on Anisakis larvae showed a similar pattern in the three populations of hakes, with the autumn-winter period reaching the highest parasitization parameters, prevalence and mean abundance, compared to the spring-summer period, with or without statistically significant differences. However, these results are not in accordance with those reported in previous studies in this and other fish species previously analysed, which reported mainly, the highest parasitization parameters during the spring season [12,18,22,36,44,45]. Only a few studies reported a higher parasitation in fish caught during the autumn season, such as in the silver hake [1,12].…”
Section: Influence Of the Of Fish Catching Season On Anisakis Parasit...contrasting
confidence: 96%
“…The very high global prevalence of Hysterothylacium and Anisakis type I larvae in the samples of European Atlantic hake and silver hake, as well as the low prevalence in the sample of European Mediterranean hake stands out. These results are in agreement with the most of the previous studies carried out on samples of the European Atlantic hake [12,22,25,27,[31][32][33][34][35][36], the silver hake [37], and the European Mediterranean hake [12,25,33,[38][39][40]. In this last case, the studies carried out in the same Mediterranean subdivision, FAO 37.1.1-Balearic, were taken into account, with the exception of the study carried out by Valero et al [26], which found a higher prevalence of parasitization in this area.…”
Section: Global Parasitizationsupporting
confidence: 93%
See 1 more Smart Citation
“…There are very few reported cases of anisakiosis in Portugal (Santos et al., 2022 ). The first case was reported in 2017 by Carmo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dead Anisakis larvae may be allergenic to previously sensitised individuals. Hake gonads are a popular Portuguese dish and this area of the fish is frequently parasitised by Anisakis (Santos et al., 2022 ). The factors outlined above indicate that the Portuguese population is at risk of exposure to this parasite.…”
Section: Introductionmentioning
confidence: 99%